Biomechanically influenced differences in O2 extraction in diagonal skiing: Arm versus leg - Björklund, G.; Stöggl, T.; Holmberg, H. C. (Medicine & Science in Sports & Exercise, 2008)
Purpose: This study aimed to determine whether the differences in oxygen extraction and lactate concentration in arms and legs during cross-country skiing are related to muscle activation or force production and how these differences are influenced by a reduction in exercise intensity.